PERTUMBUHAN TANAMAN DAN HASIL BEBERAPA VARIETAS KACANG TUNGGAK (Vigna unguiculata) YANG DITANAM PADA DUA POPULASI TANAMAN - Elfi Rahmadani; Novianti Sunarlim (Jurnal Agroteknologi, 2013)
Animal Science Faculty of Universitas Islam Negeri Sultan Syarif Kasim Riau. The objective of the research was to know the interaction between plant density and several varieties on plant growth and yield of cowpea. The experimental design was Randomized Complete Block design arranged in factorial between 2 plant densities (250.000 and 500.000 plants/ha) and 3 varieties of cowpea (KT6, KT7 and KT8) with 2 replications. The data were collected for plant height, plant dry weight, leaf area index, number and weight of nodules at 30 days after planting, number of pods/plant, number of seeds/plant, weight of 100 seeds and seed yield. Result of the research showed that increased plant density from 250.000 to 500.000 plants/ha increased leaf area index from 1,47 to 2,73 and increased seed yield from 230,2 to 271,9 g/plot. The other plant growth and yield components were not affected by different plant density. Variety affected plant dry weight, number and weight of nodules and yield components, but did not affect seed yield.